2008
DOI: 10.1002/ajp.20588
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup relations and home range use in Verreaux's sifaka (Propithecus verreauxi)

Abstract: Relationships between neighboring groups feature prominently in socioecological theory, but few empirical studies have focused on the effects of neighbors on the behavior of primates. Interactions between neighboring groups are most conspicuous during intergroup encounters, but the likelihood of encounters with neighbors can also affect ranging and activity patterns indirectly, and, as a result, behavioral patterns in areas of exclusive use may differ from those in overlap areas of adjacent home ranges. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
3
36
1
Order By: Relevance
“…Despite the limited number of observation days, the low intergroup encounter rate we report is consistent with observations in other sifaka species (Irwin 2006;Benadi et al 2008). On the other hand, the reactions of all individuals of P. coronatus observed during intergroup encounters in Badrala differed from those reported by Irwin (2006) for P. diadema in Tsinjoarivo and by Benadi et al (2008) for P. verreauxi in Kirindy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the limited number of observation days, the low intergroup encounter rate we report is consistent with observations in other sifaka species (Irwin 2006;Benadi et al 2008). On the other hand, the reactions of all individuals of P. coronatus observed during intergroup encounters in Badrala differed from those reported by Irwin (2006) for P. diadema in Tsinjoarivo and by Benadi et al (2008) for P. verreauxi in Kirindy.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the reactions of all individuals of P. coronatus observed during intergroup encounters in Badrala differed from those reported by Irwin (2006) for P. diadema in Tsinjoarivo and by Benadi et al (2008) for P. verreauxi in Kirindy. In these two studies the most frequently observed reactions were agonistic among neighboring groups.…”
Section: Discussioncontrasting
confidence: 78%
“…These issues are methodological and biological and environmental factors influencing home range estimates will not be considered here and instead dealt with elsewhere. The biological and environmental factors are group size (de Ruiter 1986;Bleisch 1995;Ostro et al 1999a;Dias & Strier 2003), diet types (Harrison, 1983), food distribution and availability (Clutton-Brock 1975;Milton 1980;Boinski 1987;Zhang 1995;Li et al 2000), water availability (Altmann & Altmann 1970;Chapman 1988), sleeping site or resting site location (Rasmussen 1979;Harrison 1983) and the presence of other groups (Wrangham et al 2007;Benadi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the length of daily travel is shortened in some species when high-quality food is rare (e.g., Trachypithecus pileatus [8], Hylobates lar [9]), conversely, other species move further to look for high-quality food resources (e.g., Colobus angolensis [10], Trachypithecus leucocephalus [11]). Ranging behavior and habitat use may also be influenced by other factors such as rainfall [12], group size [13], forest structure [4], water availability [14], location of dormitory [5], intergroup relationships [15], and parasite avoidance [16]. Nevertheless, crop-raiding primates having access to locally concentrate and high-quality food are thought to have also small home ranges that can be affected by the intensity of the human-primate conflict.…”
Section: Introductionmentioning
confidence: 99%